2006
DOI: 10.1634/stemcells.2006-0223
|View full text |Cite
|
Sign up to set email alerts
|

Essential Roles of Sphingosine 1-Phosphate/S1P1 Receptor Axis in the Migration of Neural Stem Cells Toward a Site of Spinal Cord Injury

Abstract: Neural stem/progenitor cells (NSPCs) migrate toward a damaged area of the central nervous system (CNS) for the purpose of limiting and/or repairing the damage. Although this migratory property of NSPCs could theoretically be exploited for cell-based therapeutics of CNS diseases, little is known of the mechanisms responsible for migratory responses of NSPCs. Here, we found that sphingosine 1-phosphate (Sph-1-P), a physiological lysophospholipid mediator, had a potent chemoattractant activity for NSPCs, in which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
154
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(157 citation statements)
references
References 52 publications
(99 reference statements)
2
154
1
Order By: Relevance
“…Interestingly, the addition of S1P inhibited the NPC migration elicited by a higher concentration of VPC24191 (1 to 10 mol/L; Figure 4C). These data suggest that S1P 1 R is the primary receptor involved in S1P-mediated NPC migration, in support of our previous study, 6 but also indicated that other S1PRs can regulate the S1P 1 R-mediated response.…”
Section: Migration Of Npcs Toward S1psupporting
confidence: 91%
See 3 more Smart Citations
“…Interestingly, the addition of S1P inhibited the NPC migration elicited by a higher concentration of VPC24191 (1 to 10 mol/L; Figure 4C). These data suggest that S1P 1 R is the primary receptor involved in S1P-mediated NPC migration, in support of our previous study, 6 but also indicated that other S1PRs can regulate the S1P 1 R-mediated response.…”
Section: Migration Of Npcs Toward S1psupporting
confidence: 91%
“…18,19 We previously showed a role for S1P in NPC migration toward a pathologic area of the CNS and proposed that elevation of S1P at the site of injury was a guiding factor for NPC migration. 6 Here, we reveal that S1P 2 R is a potential target for strategies aiming to increase NPC migration after brain ischemia.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…In a rat model of spinal cord injury, S1P concentration was locally increased and contributed to the attraction of neural stem cells via the S1P 1 receptor. 60 At the present time, differences in study design, outcome measures and patient populations preclude comparing the efficacy of FTY720 with other disease-modifying agents. Two phase III studies in MS are currently ongoing.…”
Section: Fingolimod (Fty720)mentioning
confidence: 99%